تأثير الإضافات العضوية والكيميائية على الخواص الميكانيكية للخلائط الإسفلتية الدافئة المحلية - سلطان بسام (Latakia University Journal -Engineering Sciences Series, 2019)
The asphalt mixture manufacturing and production process continuously seeks to reduce the mixing and compacting temperatures of the mixture in order to reduce emissions from asphalt mixtures, without significantly affecting the characteristics of these asphalt mixtures. WMA warm asphalt mixture is a modified hot asphalt mixture that is produced, brushed and compacted at a temperature of 20-40 ° C, compared to a conventional hot asphalt mixture, and at a temperature higher than boiling water. This research aims to investigate the possibility of producing warm asphalt mixtures and comparing the characteristics of warm mixtures manufactured with hot asphalt mixtures with the same materials in the design, and a comprehensive understanding of the characteristics and performance of warm mixtures in order to improve the working conditions for the production, extension and flattening of asphalt mixtures in Syria, especially the subject of mixtures Warm asphalt is relatively new in Syria. Two types of warm organic and chemical additives were used, design asphalt mixtures and determine the optimal asphalt ratio for each mixture. The results showed an increase in the ideal asphalt ratio in warm asphalt mixtures compared to hot and low stability of warm mixtures compared to hot mixes. The study found that the warm mixture designed in addition to organic by (0.3%) ideal mix achieved the specifications and stability close to the stability of hot mixtures and meet the required specification. تسعى عمليات صناعة وانتاج المجبول الاسفلتي وبشكل مستمر لتخفيف درجات حرارة خلط ورص المجبول من أجل تخفيض الانبعاثات الناتجة عن مجابل الاسفلت ، ودون التأثير بشكل كبير على خصائص هذه الخلطات الاسفلتية . إن الخلائط الإسفلتية الدافئة WMA عبارة عن خليط إسفلتي حار معدّل يتم إنتاجه و فرشه و رصه عند درجة حرارة أقل بـ 20 – 40 درجة مئوية ، مقارنة بالمجبول الإسفلتي الساخن التقليدي ، و عند درجة حرارة أعلى من درجة حرارة غليان الماء . يهدف هذا البحث إلى التحقق من إمكانية انتاج خلائط إسفلتية دافئة ومقارنة خصائص الخلائط الدافئة المصنعة مع خلائط إسفلتية حارة بنفس المواد الداخلة في التصميم ، والفهم الشامل لخصائص وأداء الخلائط الدافئة بهدف تحسين ظروف العمل الخاصة بإنتاج ومد ودحي طبقات المجبول الاسفلتي في سوريا ، وخاصة أن موضوع الخلطات الاسفلتية الدافئة يعتبر جديد نسبياً في سوريا . تم استخدام نوعين من إضافات الخلائط الدافئة العضوية والكيميائية وتصميم خلائط إسفلتية وتحديد نسبة الإسفلت المثالية لكل خلطة . بينت النتائج ازدياد نسبة الإسفلت المثالية في الخلائط الإسفلتية الدافئة مقارنة مع الساخنة ، وانخفاض ثبات الخلائط الدافئة مقارنة مع الخلطات الساخنة، كما لم تؤثر إضافات الخلائط الإسفلتية الدافئة العضوية والكيميائية على خواص الخلائط الإسفلتية بشكل كبير وبقيت قيم الانسياب والفراغات الهوائية والمليئة للخلائط المصممة ضمن الحدود المسموحة ، توصلت الدراسة إلى أن الخلطة الدافئة المصممة بالإضافة العضوية بنسبة (0.3%) خلطة مثالية محققة للمواصفات وبثبات مقارب لثبات الخلائط الحارة ومحقق لمواصفة المطلوبة.